Thermal, high pressure, and ultrasound inactivation of various fruit cultivars’ polyphenol oxidase: kinetic inactivation models and estimation of treatment energy requirement - Zawawi, Nur Aribah Fatini; Md. Hazmi, Nurul Ashikin; How, Muhammad Syahmeer; Kantono, Kevin; Silva, Filipa V. M.; Sulaiman, Alifdalino (Multidisciplinary Digital Publishing Institute, 2022)
Polyphenol oxidase (PPO) catalyses the browning reaction during fruit processing and storage. It is considered a threat to clean labels and minimally processed fruit products. Unwanted changes in fruits’ appearance and quality represent a cost to the industry. High pressure and ultrasound, in addition to thermal treatment, are effective in reducing PPO activity and producing high-quality products. PPO from different fruit cultivars behaves differently when submitted to different treatments. A systematic review was conducted, where treatment parameters, PPO inactivation data (≥80% inactivation), and kinetic inactivation parameters (rate constant (k), activation energy (Ea), D-value, and z-value) by different treatments were collected. Additionally, the estimated energy requirements for the inactivation of PPO (≥80%) by different treatments were calculated and compared. Resistance to various treatments varies between fruit cultivars. For the same temperature, the inactivation of PPO by ultrasound combined with heat is more effective than thermal treatment alone, and the high pressure combined thermal process. The majority of the thermal, HPP, and ultrasound inactivation of PPO in fruits followed first-order behaviour. Some fruit cultivars, however, showed biphasic inactivation behaviour. The estimated specific energy requirements calculated based on the mass of processed fruit sample to inactivate ≥80% polyphenol oxidase for the thermal process was 87 to 255 kJ/kg, while for high pressure processing it was 139 to 269 kJ/kg and for ultrasound it was 780 to 10,814 kJ/kg.